The Spatial Poetics and the "Murder of the Real"in Paul Auster's City of Glass* (Journal of the College of Education for Women, 2019)
Paul Auster's City of Glass is here singled out as representative of the writer's The NewYork Trilogy. All throughout his novelistic career, Auster has been working on a pseudothesisthat adheres to a certain aesthetic of disappearance. The study engages this Austerianaesthetic apropos of certain theoretical stretches such as the Emersonian "Not Me", theThoreauvian "interval" or "nowhere", the Deleuzian "nomadic trajectory", the Derridian"grammè" or "specter", and the Baudrillardian "disappearance". The city of the novel's titlingis here seen as the trope of all that which has already disappeared, and hence it is seen as thespace (mise en scène) where the perfect crime of the murder of the real is to be thoroughly redramatizedand re-thought. The writer's use of the assets of the detective genre in itspostmodernist nuances is also seen as a genuine part of this endeavour.